UNRAVELING THE MYSTERY: UNDERSTANDING ABBREVIATIONS AND ACRONYMS - Askarova Nafisa Avazovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
ABSTRACT: Abbreviations and acronyms play a crucial role in scientific literature, technical documents, and everyday communication. They enable concise and efficient communication, but they can also pose challenges for comprehension, particularly when encountering unfamiliar or ambiguous abbreviations. This article aims to shed light on the nature of abbreviations and acronyms, provide examples from various domains, and analyze their impact on effective communication.